Pelos becos da memória: uma análise da autorrepresentação negro-feminina em Conceição Evaristo - Machado, Lízia Khênya de Campos Rosa Oliveira (2021)
This dissertation intends to reflect on how Black women's literature, through Conceição Evaristo's writings, demands narratives in which a Black woman is the main character of her own story. In a time in which the current literature scene proposes discussions and the critical thought of the writing process coming from the character's perspective, and authors who are from socially and culturally marginalized spaces, it is important to reflect on the ability of this type of writing to bring visibility to places and people not or barely known in the literary world by giving them their own "standpoint speech" (RIBEIRO, 2019). Through the telling of her memories, Evaristo demands that the literature breaks with the imposed standards of prejudiced and stigmatized representations in our society. This study converses with the theories of bell hooks (2019), Lélia Gonzales (2018), Angela Davis (2016), Audre Lorde (2020), Patrícia Hill Collins (2016), Grada Kilomba (2019), Chimamanda Adichie(2019), Gayatri Spivaki (2016), Djamila Ribeiro (2019), Sueli Carneiro (2019), and so many others, and it intends to reflect about Black women's literature as resistance and a subversive way to understand Black women's identity as producers of meaningful and close-to-reader discourses. Whether through the self recognition or the recognition of the other, Becos da Memória proposes a fracture of the literary status quo, allowing other voices to be heard from a perspective that was exclusive to a white, heteronormative, and class privileged elite